Natural Ingredients with Potential as Skin Moisturizers (Body Lotion): A Narrative Literature Review - Lutfiah Nur Fitria; M. Abdul Jabar; Nurliya Dzulfiana; Sylva Ayu Widya Cahyati; Nia Yuniarsih (HM Publisher, 2022)
Hand and body lotion is a skin moisturizing cosmetic preparation that belongs to the emollient (softener) class and has several properties, namely as a source of moisture for the skin, making hands and body soft but not greasy and easy to apply on the skin. Currently, there are quite a lot of moisturizers on the market, but most of them contain several compounds that have the potential to cause interference with the barrier and skin structure. Therefore, it is necessary to carry out a comprehensive exploration effort in order to develop a moisturizer that is safer against the barrier and skin structure. Some natural ingredients that have the potential to be developed as skin moisturizers are papaya latex, yam, VCO (virgin coconut oil), and cocoa fat.